Sams teach yourself JavaScript in 24 hours - Moncur, Michael G. (Sams, 2006)
JavaScript is one of the easiest, most straightforward ways to enhance a website with interactivity. Sams Teach Yourself JavaScript in 24 Hours, 4th Edition serves as an easy-to-understand tutorial on both scripting basics and JavaScript itself. The book is written in a clear and personable style with an extensive use of practical, complete examples. It also includes material on the latest developments in JavaScript and web scripting. You will learn how to use JavaScript to enhance web pages with interactive forms, objects, and cookies, as well as how to use JavaScript to work with games, animation, and multimedia.